2012
DOI: 10.3109/00016357.2012.696691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bleaching agents and whitening dentifrices on the surface roughness of human teeth enamel

Abstract: The bleaching with 10% hydrogen peroxide and 10% carbamide peroxide did not alter the enamel surface roughness, but when the bleaching treatment was performed combined with abrasive dentifrices, a significant increase in roughness values was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
2
27
1
7
Order By: Relevance
“…All treatments were performed in constant agitation in a shaker at 37°C, during all treatment time with the mouth rinses. Furthermore, samples were stored in distilled water at 37°C during the immersion intervals then replaced on a daily basis [19]; this occurred in all groups. Color reading, microhardness, and surface roughness of each enamel sample was once more determined 24 h after the last immersion.…”
Section: Mouth Rinse Applicationmentioning
confidence: 99%
“…All treatments were performed in constant agitation in a shaker at 37°C, during all treatment time with the mouth rinses. Furthermore, samples were stored in distilled water at 37°C during the immersion intervals then replaced on a daily basis [19]; this occurred in all groups. Color reading, microhardness, and surface roughness of each enamel sample was once more determined 24 h after the last immersion.…”
Section: Mouth Rinse Applicationmentioning
confidence: 99%
“…Thus, the abrasive particles are responsible for the efficient removal of extrinsic pigments and help to prevent new staining . However, to optimize this removal, specific abrasive and chemical agents can be added to toothpaste to increase stain removal and speed up the process …”
Section: Discussionmentioning
confidence: 99%
“…1 However, to optimize this removal, specific abrasive and chemical agents can be added to toothpaste to increase stain removal and speed up the process. 32 In addition to the significance of the change in color (DE) and its coordinates (DL, Da, and Db), it is important to evaluate the clinical color difference; for this purpose, another two thresholds (perceptibility and acceptability) are helpful to clarify the visual and instrumental findings in clinical dentistry, dental research, and subsequent standardization. 21,33 Perceptibility and acceptability distinguish the color difference and show whether this difference is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their abrasiveness must be controlled. [33] Ozkan et al[34] reported that when bleaching treatment with 10% CP and 10% HP was combined with dentifrices, the roughness of the enamel surface increased. After bleaching, the use of mouthrinse and toothpaste may increase surface roughness or irregularities; as a result, the whiteness of teeth may decrease over time depending on the use of these products.…”
Section: Discussionmentioning
confidence: 99%